Socially-enhanced variants of mobile bingo game: Towards personalized cognitive and social engagement among seniors - Lee, Chien Sing *; Chan, Shanice Wei Ling *; Guy, Sheng Yee * (2017)
Elderlies often feel isolated or disregarded. This may lead to depression, lack of cognitive and social engagement. This project thus aims to engage the elderlies through three variants of a mobile bingo game application designed based on Norman’s usability principles. This paper presents the design and development of three variants of the mobile bingo game to suit the needs of senior citizens. User testing outcomes on user experience, usability and cognitive load are positive.